Factors affecting in the use of antihipertension drugs with the health belief model approach in Puskesmas Pandanwangi Malang - Ika Ratna Hidayati; Cikita Putri (Universitas Muhammadiyah Malang, 2019)
Hypertension is a condition where systolic blood pressure is 140 mmHg or higher, and diastolic blood pressure is 90 mmHg or higher. Generally, hypertension patients use captopril and Amlodipin as treatment of hypertension. It is necessary to take various efforts to improve the obedience of hypertensive patients during drug therapy. One theory studies that obedience behavior is the Health Belief Model. The HBM theory covers perceived susceptibility, severity, benefits, and barrier, along with self-efficacy. To investigate factors affecting the obedience of hypertensive patients during the antihypertensive captopril and amlodipine medications treatment in the Puskesmas Pandanwangi, Malang, this study using the approach of HBM theory and instrument. Sampling was done through a purposive and accidental sampling method. The data analysis was done through multivariate analysis, which used multiple regression to determine the effecting factors based on the HBM theory on the obedience of hypertensive patients during the antihypertensive captopril and amlodipine medications therapy. Factors of HBM theory that affect the obedience of hypertensive patients are self-efficacy, perceived severity, and perceived barrier. Whereas, the unaffected factor are perceived suspectibility and perceived benefits. Overall, factors of HBM theory affect obedience.